2015
DOI: 10.1080/00293652.2015.1015602
|View full text |Cite
|
Sign up to set email alerts
|

Becoming Christian: A Matter of Everyday Resistance and Negotiation

Abstract: The diverse appearances of church buildings, iconography and altered burial practices have commonly been used to exemplify the expansion of Christianity in early medieval Europe. Less emphasis has been placed on how the common European dealt with the Christian transformation in daily life, perhaps because of the tendency in research to distinguish ritual actions from secular. To become Christian did not necessarily entail greater religiousness or deeper religious devotion but centred rather on how people synch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…Price 2000;Spangen 2009). Studies of the Scandinavian conversions to Christianity, a focus of research in the 1980s and 1990s, have been fewer in the last decade (but see, e.g., Andrén 2013a; Kristjánsdóttir 2015;Lund 2013;Vésteinsson 2016). In the early 2000s, a group of studies pioneered new ways of incorporating written sources and archaeology in studies of pre-Christian or Old Norse worldviews.…”
Section: From Cult and Belief To Worldviews Viking Ways And Ontologiesmentioning
confidence: 99%
“…Price 2000;Spangen 2009). Studies of the Scandinavian conversions to Christianity, a focus of research in the 1980s and 1990s, have been fewer in the last decade (but see, e.g., Andrén 2013a; Kristjánsdóttir 2015;Lund 2013;Vésteinsson 2016). In the early 2000s, a group of studies pioneered new ways of incorporating written sources and archaeology in studies of pre-Christian or Old Norse worldviews.…”
Section: From Cult and Belief To Worldviews Viking Ways And Ontologiesmentioning
confidence: 99%
“…Rather, the everyday lives of people contribute to the constitutions of religious practices, believes or ideologies within the context in which everyday life is experienced. 15 These constitutive factors can be discursive structures or leading figures such as intellectuals that produce knowledge about religious experiences and practices as well as material and social conditions. The language describing categories, practices, and experiences of religion, for instance, is a tool of the discursive structures of power.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Smart, Feminism and the Power of Law, 6.21 Peskowitz, Spinning Fantasies,15. 22 James Clifford, "The Others: Beyond the "salvage" paradigm", Third Text 3/6 (1989), 126.23 Peskowitz, Spinning Fantasies, 14.24 Peskowitz, Spinning Fantasies, 17. …”
mentioning
confidence: 99%
“…Research on the early church in Iceland has been primarily historical, based in the later saga accounts and the extremely limited material on the spread of Christian practice and the institutionalization of the church in the century following the conversion (see for instance Hugason, 2000;Karlsson, 2004;Sigurôsson, 1999Sigurôsson, , 2014Stefa´nsson, 1978Stefa´nsson, , 1975. However, recent archeological work has demonstrated that although the institutional church was largely absent from Iceland, Christian household cemeteries and churches were established at a large number, perhaps the majority, of independent farms in the early 11th century (see for instance Byock et al, 2005;Gestsdo´ttir and Isaksen, 2014;Kristja´nsdo´ttir, 2004Kristja´nsdo´ttir, , 2015Sveinbjarnardo´ttir, 2009;Ve´steinsson, 2000;Zoe¨ga, 2014). With the lack of ecclesiastical organization and, probably, ordained ministers, households appear to have been largely left to their own as to how and where they buried their dead and the execution of burial rites likely were often in the hands of the household church owners themselves (Ve´steinsson, 2000;Zoe¨ga, 2014).…”
Section: Conversion and Early Christian Practice In Icelandmentioning
confidence: 99%